Karnal (Manila Cine Suerte, 1983)
A film about the tragedy of patriarchy, narrated by a 50-ish spinster daughter of one of the main figures in this story set in the 1930s in a remote Philippine provincial village.
1983 Catholic Mass Media Award for Best Film, Screenplay, Director, Lead Actor, Supporting Actor, Supporting Actress ; 1983 Manunuri ng Pelikulang Pilipino Best Actor, Supporting Actor, Supporting Actress.
English subtitles.
Inspired by "To take a life" a true legal story by Teresita Anover Rodriguez published in Mr. and Mrs. Magazine.
VHS.
Ricky Lee, screenplay ; produced by Yalung Group of Companies Int'l. Inc. ; directed by Marilou Diaz-Abaya.
Phillip Salvador, Vic Silayan, Joel Torre, Cecille Castillo.
Keywords: Feature films -- Philippines